2021
DOI: 10.1016/j.ccell.2021.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Tumor and immune reprogramming during immunotherapy in advanced renal cell carcinoma

Abstract: Highlights d Distinct CD8 + T cell phenotypes are enriched after immune checkpoint blockade (ICB) d Immune checkpoint ligands are upregulated in macrophages and tumor cells after ICB d Two cancer cell subpopulations are conserved across heterogeneous RCC tumors d Cancer cell programs drive distinct immune interactions and predict patient outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
329
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(393 citation statements)
references
References 68 publications
26
329
2
Order By: Relevance
“…It is reported that there are crosstalks between TAMs and T cells, TAMs, and tumor cells. TAMs may interact with CD8 + T cells and tumor cells through receptor-ligand pairs, such as SPP1-CD44 ( 41 ). The crosstalks between TAMs and CD8 + T cells/tumor cells may be validated by using multiplex imaging analysis ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that there are crosstalks between TAMs and T cells, TAMs, and tumor cells. TAMs may interact with CD8 + T cells and tumor cells through receptor-ligand pairs, such as SPP1-CD44 ( 41 ). The crosstalks between TAMs and CD8 + T cells/tumor cells may be validated by using multiplex imaging analysis ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PBRM1 gene had the highest mutation frequency (45.83%, 154/336), followed by SMARCA (2.68%, 9/336). In primary and advanced RCC, the expression characteristics of cancer cell subsets and immune escape are associated with PBRM1 mutations ( Bi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 2), we shortlisted 7 26,3336,38,39 out of 10 data sets for signature score calculations using SCSE 22 , AUCell 21 , ssGSEA 19 and JASMINE.…”
Section: Methodsmentioning
confidence: 99%